Analysis of Legal Protection in Indonesia in Fulfilling the Rights of Students Participating in Specialist Medical Education Programs During a Pandemic - Sola Sacra Providentia; Muhammad Rustamaji; Jadmiko Anom Husodo (SOEPRA, 2021)
Abstract: The increase in COVID-19 cases and the limited availability of personal protective equipment cause residents to be prone to contracting COVID-19 and lose some of their rights as consumers of education programs. This study analyzes the legal protection of resident’s rights fulfilment during a pandemic in Indonesia. This normative study using the statute approach is prescriptive and applied in nature. The data sources used are primary, secondary, legal and non-legal materials collected using literature study and confirmation techniques. The legal materials were analyzed using a syllogistic method of deductive mindset.The findings conclude that the resident's right fulfilment is not optimal at present. To achieve legal protection ideals, Indonesian universities as educational service providers must provide all forms of PPE and the reserves during the education period. Setting resident’s status as workers in teaching hospitals can result in the implications of providing incentives and determining working hours.Keywords: Legal Protection, Resident’s Rights, Pandemic Abstrak: Penelitian ini bertujuan untuk menganalisis perlindungan hukum di Indonesia dalam pemenuhan hak residen selama masa pandemi. Residen harus melaksanakan tugas belajar mengajar dan peningkatan kasus positif COVID-19 tidak berbanding lurus dengan ketersediaan alat pelindung diri. Residen rawan terjangkit COVID-19 dan terlanggarnya beberapa hak sebagai konsumen dari program pendidikan.Metode penelitian yang digunakan adalah normatif, dengan pendekatan  undang-undang. Sifat penelitian bersifat preskriptif dan terapan. Sumber penelitian berupa bahan hukum primer, sekunder, dan non-hukum, dengan teknik studi kepustakaan serta melakukan konfirmasi. Teknik analisis bahan hukum dengan metode silogisme melalui pola pikir deduktif.Dapat disimpulkan bahwa kondisi kekinian berkenaan pemenuhan hak residen adalah belum optimal. Dari segi idealitas perlindungan hukum, Indonesia yang saat ini menganut masih university-based, universitas sebagai penyedia jasa pendidikan harus menyediakan segala bentuk APD dan cadangannya dalam penggunaan harian selama masa pendidikan. Penetapan status residen sebagai pekerja di RS Pendidikan, dapat berimplikasi terhadap pemberian insentif dan penetapan jam kerja.Kata Kunci: Hak Mahasiswa Peserta Program Pendidikan Dokter Spesialis, Masa Pandemi, Perlindungan Hukum